Composite odontoma: An enigmatic impeder to the permanent teeth – Report of two cases with emphasis on molecular pathogenesis - Vasanthi Vinoth; Ramesh Kumar Annasamy; Rajkumar Krishnan; Velavan Krishnan (Oral Oncology Reports)
Odontome is the most common odontogenic tumour impeding the eruption of teeth. They are considered as hamartomatous malformations rather than true neoplasms. Usually, asymptomatic in nature and associated with unerupted permanent tooth. Compound and complex are the two types described by the World Health Organization. Hyperactive odontoblasts, inflammation, infection, trauma and genetic aberrations have been implicated as the factors contributing to the formation of odontoma. Aberrant Wnt/β-catenin signaling pathway and sonic hedgehog pathway were considered to contribute to the development of odontoma. We report two teenagers with complaint of unerupted permanent teeth as a consequence of hamartomatous odontoma in the path of eruption of permanent teeth.